The Relationship Between Family Environmental Support and the Responsibility of Learners in the Equivalency Education Program at PKBM Al Maula, Lima Puluh Kota Regency - Bismil Selvia; Lili Dasa Putri (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This research is motivated by the low responsibility of the learning community in the equivalency program at PKBM Al Maula, Lima Puluh Kota Regency. This research aims to (1) Describe the support of the family environment for the learning community (2) Describe the responsibility of the learning community (3) See the relationship between family environmental support and the learning community in the Equivalency Program at PKBM Al Maula, Lima Puluh Kota Regency. This research uses a quantitative approach with a correlational type. The population of this research is the learning community in the equivalency program at PKBM Al Maula, Lima Puluh Kota Regency, totaling 59 people. The research sample was taken using the Stratified Random Sampling method. The data collection technique used a questionnaire, and the data analysis technique was carried out using the Percentage Formula and Product Moment. The results of the study found that: (1) The description of the support of the family environment for the Equivalency Program at PKBM Al Maula, Lima Puluh Kota Regency is relatively low, this is evidenced by the results of the questionnaire data that has been carried out (2) Description of the responsibility of the learning community in the Equivalency Program at PKBM Al Maula, Lima Puluh Kota Regency. Fifty Cities is classified as low, (3) There is a significant relationship between family environmental support and the responsibility of residents studying the equivalency program at PKBM Al Maula, Fifty Cities Regency.